TECHNOLOGICAL PROFESSIONALIZATION AND HUMAN DEVELOPMENT IN GRADUATES OF THE VOLUNTARY MILITARY SERVICE AT THE INSTITUTE OF HIGHER PUBLIC TECHNOLOGICAL EDUCATION OF THE ARMED FORCES, LIMA, 2019 - Vélez Carrasco, Manuel Antonio (2021)
This article aims to determine the relationshipthat exists between technological professionalization andhuman development in service graduatesmilitary volunteer at the Institute of Higher EducationTechnological Public of the Armed Forces, Lima,2019. In order to deepen the analysis and theinterpretation of the results, the approach was usedquantitative, correlational in scope, non-designexperimental and cross-sectional, since they were collecteddata at a single point in time, by samplingprobabilistic, since the sample was 234 studentsdischarged from voluntary military service. to sampleIn the study, a 24-item questionnaire was applied, within order to collect data on the variables. In addition,Cronbach's Alpha coefficient was used to see theinternal consistency of the instrument; statistics were used to organize and estimate the statisticiansdescriptive; and, for the contrast of the hypotheses, it was appliedthe statistical test of the correlation coefficient r ofPearson, in order to observe the correlation betweenthe two quantitative variables. The results obtainedwere analyzed at the descriptive and inferential levelaccording to the objectives and hypotheses formulated. in whatRegarding technological professionalization, 46.2%He stated that the level of studies is good; 23.1%,which is excellent; 17.1%, which is bad; 12.03%, which isregular; and only 1.7% indicated that the study variable isVery bad. Likewise, in human development, 38.9%do you agree; 26.5% totally agree; the 19.7%, in disagreement; 13.7% are indifferent; and only 1.3%totally disagree.